Odpowiedź :
a) (x+2) (x-3) = 0 dla -2
(-2+2) (-2-3) = 0
0 × (-5) = 0
odp: -2 spełnia równanie
b) x-13 = 2x-10 dla -3
(-3)-13 = 2×(-3)-10
-16 = -6-10
-16 = -16
odp: -3 spełnia równanie
c) 5x+3 = 13 dla 2
5×2+3 = 13
10+3 = 13
13 = 13
odp: 2 spełnia równanie
d) -x-13 = 2x+1 dla 5
-5-13 = 2×5+1
-18 = 10+1
-18 = 11
odp: 5 nie spełnia równania
Odpowiedź:
[tex]a](x+2)(x-3)=0\\ podstawiamy-2\\ (-2+2)(-2-3)=0\\(0)*(-5)=0\\0=0\\prawda\\b] x-13=2x-10\\podstawiamy -3\\-3-13=2*(-3)-10\\-16=-6-10\\-16=-16\\prawda\\c]5x+3=13\\podstawiamy 2\\5*2+3=13\\10+3=13\\13=13\\prawda\\d]-x-13=2x+1\\podstawiamy 5\\-5-13=2*5+1\\-18=11\\falsz[/tex]
Szczegółowe wyjaśnienie: